Present‐Day Crustal Deformation of Continental China Derived From GPS and Its Tectonic Implications - Wang, Min; Shen, Zheng‐Kang (Journal of geophysical research. Solid earth, 2020)
We process rigorously GPS data observed during the past 25 years from continental China to derive site secular velocities. Analysis of the velocity solution leads to the following results. (a) The deformation field inside the Tibetan plateau and Tien Shan is predominantly continuous, and large deformation gradients only exist perpendicular to the Indo‐Eurasian relative plate motion and are associated with a few large strike‐slip faults. (b) Lateral extrusions occur on both the east and west sides of the plateau. The westward extrusion peaks at ~6 mm/yr in the Pamir‐Hindu Kush region. A bell‐shaped eastward extrusion involves most of the plateau at a maximum rate of ~20 mm/yr between the Jiali and Ganzi‐Yushu faults, and the pattern is consistent with gravitational flow in southern and southeastern Tibet where the crust shows widespread dilatation at 10–20 nanostrain/yr. (c) The southeast borderland of Tibet rotates clockwise around the eastern Himalaya syntaxis, with sinistral and dextral shear motions along faults at the outer and inner flanks of the rotation terrane. The result suggests gravitational flow accomplished through rotation and translation of smaller subblocks in the upper crust. (d) Outside of the Tibetan plateau and Tien Shan, deformation field is block‐like. However, unnegligible internal deformation on the order of a couple of nanostrain/yr is found for all blocks. The North China block, under a unique tectonic loading environment, deforms and rotates at rates significantly higher than its northern and southern neighboring blocks, attesting its higher seismicity rate and earthquake hazard potential than its neighbors. Key Points Production of a GPS velocity solution in China with rigorous processing and accounting for effects of large earthquakes Comprehensive analysis of distributed deformation within Tibetan plateau and Tien Shan and block‐like deformation for the rest of region Quantification of two‐way extrusion of Tibetan plateau and clockwise rotation of its southeast borderland